Curriculum Development in Language Teaching - Richards J. C. Jack (Cambridge Language Education)
This text provides a systematic introduction to the issues involved in developing, managing, and evaluating effective language programs. Key stages in the curriculum development process are examined, including situation analysis, needs analysis, goal-setting, syllabus design, materials development and adaptation, teaching and teacher-support, and evaluation. Taken into account are such factors as program content, program context, learner needs, teaching aims and objectives, and the selection of instructional materials. Practical task and discussion activities throughout the book enable it to be used both in in-service courses and as a reference text for coordinators, teachers, and program administrators. Professor Jack C. Richards is an internationally recognized authority on methodology, teacher development, and materials design, and has taught in universities in the United States, Hong Kong, Singapore, New Zealand, Canada, Indonesia, and Brazil. He has lectured and consulted in East Asia, North and South America, Europe, and the Middle East. Professor Richards' many successful texts and teacher-training books include Approaches and Methods in Language Teaching, now available in a second edition, and Beyond Training.